Exopolysaccharide (EPS) Producing Bacteria of Sundarbans Mangrove Forest Soil (Plant Tissue Culture and Biotechnology, 2022)
The present study was undertaken to investigate the exopolysaccharide (EPS) producing bacteria from Sundarbans Mangrove Forest (SMF) soil of Bangladesh. The pH and aerobic heterotrophic bacterial counts of the soil samples ranged from 5.83 to 7.77 and 0.87 × 107 to 7.2 × 107 cfu/g, respectively. Potential 18 EPS producing bacterial isolates were selected for detailed study among which 15 were provisionally identified as members of the genus Bacillus, 2 were recognized as Dinococcus sp. and another one as Micrococcus sp. The genus Bacillus includes 7 distinct species viz. B. stearothermophilus, B. subtilis, B. brevis, B. marinus, B. schlegelli, B. pumilus and B. globisporous. The highest EPS production was found in the LB medium. The pHs of 6.5-7.5, 0% salinity, and 37°C temperature were found to be optimum for better growth of EPS producing bacteria. The three EPS producing bacterial isolates i.e. B. pumilus, B. globisporus and B. strearothermophilus were further confirmed through 16S rDNA sequence analysis. The culture and sensitivity (C/S) test results revealed streptomycin (S 10) as the most effective antibiotic to control the tested bacterial isolates.Plant Tissue Cult. & Biotech. 32(2): 145-156, 2022 (December)